The evental subject the concept of the human person in Alain Badiou's event metaphysics - Masong, Kenneth C. (2011)
An individual is not a subject. What constitutes the subject as subject is the happening of event and the way this happening transforms the insularity of the individual into the “eventality” of the subject. For Alain Badiou (b.1937), a true subject is one that is subjectivized by the happening of the event and the subject’s continuous fidelity to this same event. This essay explores the concept of the human person in Alain Badiou’s philosophy. In order to achieve this, a broad overview of Badiou’s Ontology of the Event is necessary in order to locate his philosophical anthropology. What follows is a discussion of Badiou’s dynamic conception of an individual as a becoming-subject in relation to an event, a relation characterized by fidelity to the event. This unique philosophy of the human person finds its singular exemplar in the New Testament figure of St. Paul of Tarsus. The conclusion of the essay brings Badiou’s philosophy of the event, subject and truth into the domain of religious discourse where, interestingly, his philosophy finds a genial fertile ground for further exploration.
Keywords: Metaphysics; Agent (Philosophy); Humanity; Badiou, Alain -- Criticism and interpretation